Analgesic Efficacy of Dexamethasone and Dexmedetomidine as an Adjuvant to Bupivacaine Infiltration in Unilateral Cleft Lip Surgery: A Randomized, Double-Blinded Study - Sedighe Shahhosseini; Mohammad Montasery; Iman Raeisi; Amir Shafa; Mohammad Omid; Mehrdad Memarzadeh; Yasaman Borghei (Archives of Anesthesia and Critical Care, 2024)
Background: In the majority of cases, the treatment method for Cleft lip is surgery. Providing adequate pain control during and after surgery for children, is too important. Also, different methods are used for pain relief like analgesic prescription and nerve block and different adjuvants can be added to anesthetics to reduce pain. Aims: This trial was aimed to compare the analgesic effect of Bupivacaine with or without dexmedetomidine or dexamethasone for cleft lip surgery. Methods: This study is a prospective, double-blinded, randomized trial which conducted on 75 pediatrics, aged between 3 to 10 months, who needed unilateral cleft lip surgery. Patients were divided into 3 groups (n=25 in each group). Children in group A, were given a combination of bupivacaine and 0.5 µg/kg of dexmedetomidine, those in group B, 0.1 mg/kg of dexamethasone as an adjuvant to bupivacaine, and in group C, plain 1 cc of bupivacaine 0.5% was injected in the operation site. Outcomes were assessed via FLACC and WATCHA scores. Results: The mean age among children was 4.3 ±1.29 months and mean weight was 6.3± 1.09 kg. Pain score and frequency of analgesic request intra and post-operation in group A was lower than others (p<0.0001). Also, FLACC and WATCHA scores were significantly lower in group A (p<0.0001) and parental and surgeon satisfaction was higher in group A (p<0.05). Conclusion: Our study showed that, dexmedetomidine as an adjuvant to bupivacaine 0.5% is more effective to improve the analgesia, in children who underwent unilateral cleft lip surgery.